Unique rumen micromorphology and microbiota–metabolite interactions: features and strategies for Tibetan sheep adaptation to the plateau - Chen, Qianling; Sha, Yuzhu; Liu, Xiu; He, Yanyu; Chen, Xiaowei; Yang, Wenxin; Gao, Min; Huang, Wei; Wang, Jiqing; He, Jianwen; Wang, Lei (Frontiers in Microbiology, 2024)
The rumen microbiota, which is a known as the host's symbionts to its host and consists of important functional substances, plays an important role in the animal body and isrepresents a new perspective in the study of animal adaptive evolution in animals. This study demonstrates found that: the rumen nipple height and cuticle thickness of the Tibetan sheep were significantly greater higher than those of the Hu sheep (P<0.01), and that the digestion and absorption of forage were greater stronger. The levels of Carbohydrate metabolism, Lipid metabolism and Protein turnover were increased in Tibetan sheep, which enabled them to efficiently ferment efficiently, and utilize forage, and absorb metabolic volatile fatty acids (VFAs)VFAs. Tibetan sheep rumen metabolites were related to immune function and energy metabolism, which were involved in regulating the rumen growth, and development and gastrointestinal homeostasis. Thus, compared with Hu sheep, Tibetan sheep have more rumen papilla and cuticle corneum, and the synergistic effect of the microbiota and its metabolites is a characteristic and strategy for adapting to high-altitude environments. having a higher rumen papilla and cuticle and the synergistic effect of microbiota and their metabolites are a characteristic and strategy for the adaptation of Tibetan sheep to the plateau environment compared to Hu sheep.